The effect of a prostaglandin E1 derivative on the symptoms and quality of life of patients with lumbar spinal stenosis - Takahashi, Jun; Hirabayashi, Hiroki; Hashidate, Hiroyuki; Ogihara, Nobuhide; Mukaiyama, Keijiro; Kato, Hiroyuki; Kobayashi, Hirokazu; Wakabayashi, Shinji; Deguchi, Masao; Ito, Hidehiro; Mogami, Yuji; Tanikawa, Hirotaka; et al. (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2013)
Quality of life (QOL) is a concern for patients with lumbar spinal stenosis (LSS). In this study, QOL was examined using the 5-item EuroQol (EQ-5D). QOL and activities of daily living (ADL) were surveyed for 91 patients who visited 18 medical institutions in our prefecture and were diagnosed with LSS-associated intermittent claudication. A second survey was performed after ≥6weeks for 79 of the subjects to evaluate therapy with limaprost (an oral prostaglandin E1 derivative) or etodolac (an NSAID). Symptoms, maximum walking time, QOL, ADL items, and relationships among these variables were investigated for all 91 patients. Leg pain, leg numbness, and low back pain while walking were surveyed by use of VAS scores (0–100). Leg pain, leg numbness, and low back pain while walking (VAS ≥25) were present in 83.5, 62.6, and 54.9% of the patients in the first survey, and approximately half of the patients had a maximum walking time <15min. The mean EQ-5D utility value for QOL was 0.59±0.12. This value was significantly associated with maximum walking time (p=0.030) based on classification of patients into groups with walking times <7.5, 7.5–15, 15–30, and >30min, showing that maximum walking time affected health-related QOL. Of the 79 patients who completed the second survey, 56 had taken limaprost and 23 (control group) had received etodolac. Limaprost improved possible walking time, reduced ADL interference, and significantly increased the EQ-5D utility score, whereas no significant changes occurred in the control group. Maximum walking time was prolonged by ≥10min and the EQ-5D utility value was improved by ≥0.1 points in significantly more patients in the limaprost group than in the control group. According to the findings of this survey, at an average of 8weeks after administration limaprost improved symptoms, QOL, and ADL in LSS patients whereas treatment with an NSAID reduced pain but did not have any other effects.